Measuring Students’ Attitude Towards Chemistry: The Strengthening Mathematics and Science Education’s Approach - Muhammed, Ashiat Bolanle (Unnes Science Education Journal, 2021)
Students’ academic success is dependent on several affective factors. Critical among these factors is students’ attitude. Hence, the need to view attitude as an outcome rather than influence, becomes imperative. The Activity, Student-centered, Experiment, Improvisation-Plan, Do, See, Improve (ASEI-PDSI) approach is a pedagogical model for strengthening mathematics and science education in Nigeria and thought to promote positive attitudinal change towards learning. Hence, this study investigated the effects of ASEI-PDSI approach on Senior School students’ attitude towards Chemistry. The study was a quasi-experimental one, the sample comprised 139 SSI students from two randomly selected co-educational schools in Ilorin, Nigeria. The ASEI-Instructional Package (ASEI-IP) was the stimulus instrument while the Attitude Towards Chemistry Scale (ATCS) was the test instrument. The reliability of ATCS was found to be 0.68. The data gathered were analysed using Analysis of Covariance and t-test statistics. The finding revealed that ASEI-PDSI approach did not bring about any significant change in attitude towards chemistry. The study concluded that ASEI-PDSI approach might not promote students’ attitude towards chemistry all the time.